Solid-phase extraction : principles and practice / E.M. Thurman, M.S. Mills. - Thurman, E. M. 1946- (Chemical analysis, 1998)
Solid Phase Extraction (SPE) is a method of preparing samples for analysis. The technique involves purifying and concentrating a sample using a disposable column. This book explains how solid-phase extraction works and provides detailed applications of SPE in clinical, environmental, and natural product chemistry.